Social Innovation of Tourism Village: Asset-based Community Development in East Rombiya Village, Madura, Indonesia - Salam, Abdus; Sihidi, Iradhad Taqwa; Akmalia, Naila Febrina; Hardini, Hevi Kurnia (Faculty of Social and Political Sciences - UIN Walisongo Semarang, 2025)
East Rombiya Village, Sumenep, Madura, is a compelling example of a region actively advancing sustainable village tourism by leveraging its local potential. This study aims to analyze the social innovation initiated by the Village Government through the Village-owned Enterprises (BUMDes) in developing the